Q. 24.1( 215 Votes )

Simplify and expr

Answer :

(i) Formula: am ÷ an = a(m-n)

By using above formula in question:

(-4)5 ÷ (-4)8

= (-4)5-8

= (-4)-3

= 1/(-4)3

= -1/64

(ii) Formula: (am)n = amn

By using above formula in question:

(iii) Formula:- am × bm = (a × b)m

Using this formula:

(iv) Formula:- am ÷ an = a(m-n)

am × an = a{m+n}

By using above formula in question:

(3-7÷ 3-10) × 3-5

= (3 (-7+10)) × 3-5

= 33 × 3-5

= 3 (3-5)

= 3-2

= 1/32
= 1/9

(v) 2-3 × (-7)-3

By using the formula,
am × bm = (a × b)m

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in the blankNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

If abc is a threeNCERT - Mathematics Exemplar

Let abc be a threNCERT - Mathematics Exemplar

The sum of all nuNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

Let abc be a threNCERT - Mathematics Exemplar